Pengaruh Media Visual Pada Materi Menyusun Huruf Nama Benda Terhadap Motivasi Belajar Siswa - Windi Pujasari; Ani Sri Mulyani; Hani, Umi (Prodi PGMI STAI Sabili Bandung, 2023)
Currently grade 1 students sometimes feel lazy in understanding learning material and writing. According to the researchers, this is because students at this age have not been confronted directly with things that are real or contextual. Moreover, seeing the characteristics of grade 1 elementary school children is concrete operational, that is, they must be confronted with something real. The purpose of this study was to determine the effect of visual media on students' motivation in the material